(untitled) (Swiss Medical Weekly, 2018)
OBJECTIVES To assess the use of the Clinical EULAR Sjögren’s Syndrome Disease Activity Index (ClinESSDAI), a version of the ESSDAI without the biological domain, for assessing potential eligibility and outcomes for clinical trials in patients with primary Sjögren’s syndrome (pSS), according to the new ACR-EULAR classification criteria, from the UK Primary Sjögren’s Syndrome Registry (UKPSSR). METHODS A total of 665 patients from the UKPSSR cohort were analysed at their time of inclusion in the registry. ESSDAI and ClinESSDAI were calculated for each patient. RESULTS For different disease activity index cut-off values, more potentially eligible participants were found when ClinESSDAI was used than with ESSDAI. The distribution of patients according to defined disease activity levels did not differ statistically (chi2 p = 0.57) between ESSDAI and ClinESSDAI for moderate disease activity (score ≥5 and <14; ESSDAI 36.4%; ClinESSDA 36.5%) or high disease activity (score ≥14; ESSDAI 5.4%; ClinESSDAI 6.8%). We did not find significant differences between the indexes in terms of activity levels for individual domains, with the exception of the articular domain. We found a good level of agreement between both indexes, and a positive correlation between lymphadenopathy and glandular domains with the use of either index and with different cut-off values. With the use of ClinESSDAI, the minimal clinically important improvement value was more often achievable with a one grade improvement of a single domain than with ESSDAI. We observed similar results when using the new ACR-EULAR classification criteria or the previously used American-European Consensus Group (AECG) classification criteria for pSS. CONCLUSIONS In the UKPSSR population, the use of ClinESSDAI instead of ESSDAI did not lead to significant changes in score distribution, potential eligibility or outcome measurement in trials, or in routine care when immunological tests are not available. These results need to be confirmed in other cohorts and with longitudinal data.